Organizational Management of Arabic Matriculation Program at IAIN Sultan Amai Gorontalo - Maryam Nur Annisa; Zakiyah Arifa; Ratni Bt. H. Bahri; Mukhtar I. Miolo (Sustainable, 2024)
The main role of the Arabic matriculation program is to prepare new students who have diverse educational backgrounds, so that their basic Arabic language skills can be equalized. The purpose of this study is to understand how the organizational management of the Arabic language matriculation program at IAIN Sultan Amai Gorontalo's Arabic Language Education Study Program. This research applies qualitative method. The data collection process was conducted through interview techniques and documentation recording. After the data is collected, data analysis is carried out with stages: 1) reducing data, 2) presenting data, and 3) drawing conclusions or verifying, from this study it can be concluded that the Arabic matriculation program has succeeded in equalizing the basic Arabic language skills for new students by measuring initial abilities, selecting appropriate teaching materials, class division, implementation, and evaluation. The result of this research are delegation of authority in this program is listed in the decision letter issued by the study program, complete with the duties and authority of each individual. Decision-making is based on deliberation between the study program and the management of the student association. Span of control is maintained through regular meetings, reporting, and effective communication between all relevant parties. The organizational structure involving the Study Program, the Department Student Association, the head of the language division, and tutors has a clear role in organizing and implementing the program.